Characterization of Leader Processing Shows That Partially Processed Mersacidin Is Activated by AprE After Export - Viel, Jakob H.; van Tilburg, Amanda Y.; Kuipers, Oscar P. (Frontiers in Microbiology, 2021)
The ribosomally synthesized and post-translationally modified peptide mersacidin is a class II lanthipeptide with good activity against Gram-positive bacteria. The intramolecular lanthionine rings that give mersacidin its stability and antimicrobial activity, are specific structures with potential applications in synthetic biology. To add the mersacidin modification enzymes to the synthetic biology toolbox, a heterologous expression system for mersacidin in Escherichia coli has recently been developed. While this system was able to produce pre-mersacidin that could be activated by Bacillus amyloliquefaciens supernatant, and showed that mersacidin was activated in an additional proteolytic step after transportation out of the cell, it lacked a mechanism for clean and straightforward leader processing. Here, the protease responsible for activating (pre)mersacidin was identified and heterologously produced in E. coli, improving the previously reported heterologous expression system. By screening multiple proteases, the stringency of proteolytic activity directly next to a very small lanthionine ring is demonstrated, and the full two-step proteolytic activation of mersacidin was elucidated. Additionally, the effect of partial leader processing on diffusion and antimicrobial activity is assessed, shedding light on the function of two-step leader processing.